Investigating effective factors on improvement and development of medicinal Pants in Iran (case study Isfahan city) - Seyed Fathollah Amiri Aghdaie; Hossein zare Zardeini (تحقیقات بازار یابی نوین, 2014)
Using plants has a long history in treatment. Herbal medicine has always been one of the main pillars of the famous medical school in ancient civilization. Nowadays also, a high Volume of trade in the world is belongs to medicinal because of its current importance. However a very few studies have been performed in the field of medicinal plants marketing In this study we have tried to determine the factors that can help to improve and develop The market of medicinal plants in Iran. The paper is descriptive-cognition and the related Information for this scope have been collected by using library resources such as books And scientific journals, moreover for collecting necessary data in order to confirm or reject Research hypothesis a questionnaire made by researchers have been used, data analyzed with SPSS software and presumption statistical methods. Sample 57 consists of medicinal plants sellers(druggist), pharmacists and doctors choose with random sampling. The result showed that all the variables factors of the study can help to improve and expand medicinal market.